2022
DOI: 10.1038/s41598-022-05507-1
|View full text |Cite
|
Sign up to set email alerts
|

Entropy generation from convective–radiative moving exponential porous fins with variable thermal conductivity and internal heat generations

Abstract: The performance and thermal properties of convective–radiative rectangular and moving exponential porous fins with variable thermal conductivity together with internal heat generation are investigated. The second law of thermodynamics is used to investigate entropy generation in the proposed fins. The model is numerically solved using shooting technique. It is observed that the entropy generation depends on porosity parameter, temperature ratio, temperature distribution, thermal conductivity and fins structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 32 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…The combination of nanomolecules in the basefluid runs to a difference in the characteristics thermophysically. Table 1 summarises the relevant parameters for PENF (Reddy et al, 2014;Din et al, 2022).…”
Section: Framed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of nanomolecules in the basefluid runs to a difference in the characteristics thermophysically. Table 1 summarises the relevant parameters for PENF (Reddy et al, 2014;Din et al, 2022).…”
Section: Framed Modelmentioning
confidence: 99%
“…Ahmad et al (Ahmad et al, 2022a) studied the unsteady 3D-bio convective movement of HNFs by an exponentially widening sheet with VTC and chemical reaction. Din et al (Din et al, 2022) assumed the entropy generation from convective released moving exponential porous fins with VTC and interior temperature compeers. For more details see Refs (Akgül et al, 2022;Attia et al, 2022;Ahmad et al, 2022b;Bilal et al, 2022;Qureshi et al, 2022;Safdar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Using the Runge-Kutta method the effects of magnetic field and convection on radiating radial porous fins have been discussed. 37,38 The performance of the radial fin surface in the presence of a magnetic field to that in the absence of a magnetic field has also been compared in the same articles. A moving porous fin with convex, parabolic, concave, and trapezoidal profiles wetted by a hybrid nanofluid has been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Sreedevi and Reddy 36 examine the effects of magnetohydrodynamics on fins under various circumstances. Using the Runge–Kutta method the effects of magnetic field and convection on radiating radial porous fins have been discussed 37,38 . The performance of the radial fin surface in the presence of a magnetic field to that in the absence of a magnetic field has also been compared in the same articles.…”
Section: Introductionmentioning
confidence: 99%
“…e temperature distribution, radiation, and convection in longitudinal fins with heat transfer and heat generation have been extensively studied [22][23][24]. It is concluded that the temperature at the tip of the fin increases with the decrease in the radiation-conduction parameter and Peclet number with a rise in the heat production gradient.…”
Section: Introductionmentioning
confidence: 99%